Effectiveness of Problem-Based Learning Model in Science Learning: A Meta-Analysis Study - Sutriawan, Agus; Irvan, Irvan (STKIP Muhammadiyah Kuningan, 2023)
This study aims to determine; 1) is there a contribution between arm strength and the The purpose of this study is to find out how well high school students in 2023 can throw shot put. This research is a type of descriptive research using a survey approach. The data collection method uses a shot put throwing ability test. The population for this study was high school students in 2023. There were 56 students, and the researcher used a total sample technique to collect their data. Methods of data analysis using descriptive analysis. The results of the study showed that the students' shot put ability at SMA Negeri 3 Pinrang was in the moderate category